The adjustment of the deaf to a hearing world - Nagdee, Zanunissa (Not Specified, 2023)
The writer wishes to thank the staff of the Dominican School for the Deaf at Wittebome with whose ample assistance she was able to write the thesis. They allowed her to be present during lessons, attend staff discussions, consult the records of pupils and borrow books and pamphlets. In addition, it was through their help that she was able to visit the homes of past and present pupils. The parents of the deaf pupils and the deaf adults with whom the writer came into contact were very helpful and for this she is grateful. The writer wishes to thank the branch secretary of the National Council for the Deaf at Woodstock who allowed her to attend the social evenings. She also wishes to express thanks to managers of the Cape Footwear Industry whose workers she interviewed. Finally, it is although the generous co-operation of many deaf children and adults that she was able to have an insight into their problems and difficulties.